Docosahexaenoic Acid Reduces the Incidence of Early Afterdepolarizations Caused by Oxidative Stress in Rabbit Ventricular Myocytes - Zhao, Zhenghang; Wen, Hairuo; Fefelova, Nadezhda; Allen, Charelle; Guillaume, Nancy; Xiao, Dandan; Huang, Chen; Zang, Wei-Jin; Gwathmey, Judith K.; Xie, Lai-Hua (Frontiers in Physiology, 2012)
Accumulating evidence has suggested that ω3-polyunsaturated fatty acids (ω3-PUFAs) may have beneficial effects in the prevention/treatment of cardiovascular diseases, while controversies still remain regarding their antiarrhythmic potential. It is not clear yet whether ω-3 PUFAs can suppress early afterdepolarizations (EADs) induced by oxidative stress. In the present study, we recorded action potentials (APs) using the the patch-clamp technique in ventricular myocytes isolated from rabbit hearts. The treatment of myocytes with H2O2 (200 μM) prolonged AP durations (APDs) and induced EADs, which were significantly suppressed by docosahexaenoic acid (DHA, 10 or 25 µM) (n = 8). To reveal the ionic mechanisms, we examined the effects of DHA on L-type calcium currents (ICa.L), late sodium (INa), and transient outward potassium currents (Ito) in ventricular myocytes pretreated with H2O2. H2O2 (200 μM) increased ICa.L by 46.4% from control (-8.4 ±1.4 pA/pF) to a peak level (-12.3±1.8 pA/pF, n=6, p < 0.01) after 6 min of H2O2 perfusion. H2O2-enhanced ICa.L was significantly reduced by DHA (25 μM) (-7.1 ± 0.9 pA/pF, n = 6, p < 0.01). Similarly, H2O2 increased the late INa (-3.2 ± 0.3 pC) from control level (-0.7 ± 0.1 pC). DHA (25 μM) completely reversed the H2O2-induced increase in late INa (to -0.8 ± 0.2 pC, n=5). H2O2 also increased the peak amplitude of and the steady state Ito from 8.9 ±1.0 and 2.16 ± 0.25 pA/pF to 12.8 ±1.21 and 3.13 ± 0.47 pA/pF respectively (n=6, p < 0.01, however, treatment with DHA (25 μM) did not produce significant effects on current amplitudes and dynamics of Ito altered by H2O2. In addition, DHA (25 μM) did not affect the increase of intracellular reactive oxygen species (ROS) levels induced by H2O2 in rabbit ventricular myocytes. These findings demonstrate that DHA suppresses exogenous H2O2-induced EADs mainly by modulating membrane ion channel functions, while its direct effect on ROS may play less prominent role.